2008
DOI: 10.1530/eje-07-0629
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype correlation in a family with primary cortisol resistance: possible modulating effect of the ER22/23EK polymorphism.

Abstract: Objective: Glucocorticoid resistance is a rare sporadic or familial condition that is characterized by generalized, partial resistance to glucocorticoids. It is caused by a mutation in the glucocorticoid receptor-a (GR-a) gene. We aimed to understand the reasons for different phenotypes (severe to asymptomatic) observed in a family with primary cortisol resistance. Design: The genotype leading to cortisol resistance in the family members was investigated and correlated to the clinical phenotype. Method: Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…LDL increases with age, and a higher baseline LDL may be modified to a greater degree by the ER22/23EK polymorphism (45). Beneficial effects on LDLC are not universal and one study confirmed benefit by trend, but failed to reach statistical significance (21,44,46,47). The ER22/23EK polymorphism was rare and it is important to recall that we present only descriptive statistics.…”
Section: Discussionmentioning
confidence: 94%
“…LDL increases with age, and a higher baseline LDL may be modified to a greater degree by the ER22/23EK polymorphism (45). Beneficial effects on LDLC are not universal and one study confirmed benefit by trend, but failed to reach statistical significance (21,44,46,47). The ER22/23EK polymorphism was rare and it is important to recall that we present only descriptive statistics.…”
Section: Discussionmentioning
confidence: 94%
“…Phenotypes may vary even among patients and relatives with the same disease-causing mutation (18,20,26). The characteristically low plasma renin and aldosterone levels in glucocorticoid resistance have been ascribed to the high cortisol level.…”
Section: Discussionmentioning
confidence: 99%
“…In glucocorticoid resistance, inappropriate binding of cortisol to the mineralocorticoid receptor causes increased sodium reabsorption and extracellular volume expansion, resulting in low renin and aldosterone levels and contributing to the elevated blood pressure. At least 14 mutations in NR3C1 in regions that encode the DNA-or hormone-binding domain of hGRa have been previously reported in patients with generalized glucocorticoid resistance (1,2,6,7,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26). Eleven of these mutations represent amino acid substituting point mutations in exons 4, 5, 7, 8, and 9a (6, 7, 12, 13, 14, 15, 16, 17, 18, 19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are significant differences in how individuals perceive and interpret stressors, and the encoding of memories of past stressful events influences one's response to future stressors (Buchanan and Lovallo, 2001; Marti et al, 2001; Wolf, 2003). Genetic factors also can contribute to individual differences in HPA function and stress responsivity (Kuningas et al, 2007; Ising et al, 2008; Peeters et al, 2008; Raef et al, 2008; Duan et al, 2009). Recognizing the potential for an interaction between glucocorticoid gene polymorphisms and environment in influencing physiological and behavioral phenotypes is also important (Bet et al, 2008).…”
Section: Individual Differences In Hpa Axis Function As a Source Of Vmentioning
confidence: 99%